FRAMING ONLINE SELF-DISCLOSURE: HOW PRIVACY AND PUBLICITY ARE REPRESENTED IN MAINSTREAM NEWSPAPERS - Ashuri, Tamar; Halperin, Ruth (AoIR Selected Papers of Internet Research, 2014)
The Web 2.0 era is characterized by a move from a relatively anonymous environment to one in which users are increasingly identifiable. A parallel phenomenon has been increased self-disclosure online, whereby identified individuals are distributing personal information in networked platforms. Since ‘privacy by obscurity’ becomes obsolete, and as control over personal information continues to erode (Zimmer and Hoffmann, 2012), the ability of marketers, employers, voyeurs and other concerned parties to link dispersed digital information and process it for different purposes has reached unprecedented magnitudes (Nissenbaum, 2010). Questions therefore arise regarding the implications of online self-disclosure, and how various agents (e.g. firms, governments, and individual users) manage the risks associated with it. This study attempts to contribute to the theoretical understanding and empirical investigation of online self-disclosure and its implications by examining the construction of various issues regarding self-disclosure in Israel’s mainstream media. The analysis of media texts aims to evaluate the extent to which media representation of topics surrounding online self-disclosure in the web 2.0 era contributes to reflexive and critical public debate concerning these performances. The social and political significance of such debate is pivotal for Internet users, as it may well influence their perceptions of the online environment and the characteristics of their enactments within it.